2019
DOI: 10.1002/cssc.201901693
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Synthesis of Bright Green Fluorescent Nitrogen‐Doped Carbon Quantum Dots from Alkali Lignin

Abstract: Sustainable, inexpensive, and environmentally friendly biomass waste can be exploited for large‐scale production of carbon nanomaterials. Here, alkali lignin was employed as a precursor to synthesize carbon quantum dots (CQDs) with bright green fluorescence through a simple one‐pot route. The prepared CQDs had a size of 1.5–3.5 nm, were water‐dispersible, and showed wonderful biocompatibility, in addition to their excellent photoluminescence and electrocatalysis properties. These high‐quality CQDs could be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 61 publications
5
74
0
Order By: Relevance
“…More recently, Zhang et al also reported the preparation and LCQDs with bright green fluorescence from kraft lignin by a simple one-pot method. 91 In this case the prepared LCQDs revealed notable luminescence properties to be applied in cell imaging applications and also as ion detection sensors, with high sensitivity towards silver ion (Ag + ) ( Fig. 4c-e), comparable to those reported previously for other CQDs based on foodstuff precursors such as broccoli.…”
Section: Sensor and Biosensing Applicationssupporting
confidence: 81%
See 2 more Smart Citations
“…More recently, Zhang et al also reported the preparation and LCQDs with bright green fluorescence from kraft lignin by a simple one-pot method. 91 In this case the prepared LCQDs revealed notable luminescence properties to be applied in cell imaging applications and also as ion detection sensors, with high sensitivity towards silver ion (Ag + ) ( Fig. 4c-e), comparable to those reported previously for other CQDs based on foodstuff precursors such as broccoli.…”
Section: Sensor and Biosensing Applicationssupporting
confidence: 81%
“…Lignin-based carbon quantum dots (LCQDs) have emerged as a new class of materials in applications such as metal ion sensors, bio-imaging and biosensors. 43,[86][87][88][89][90][91] Most of the sensors formulated on LCQDs work based on the quenching or the prevention of the quenching of fluorescence emission in the presence of certain analytes such as a metal ions. 92 Among the different quenching mechanisms, LCQDs work basically by static quenching pathways, where the interaction of LCQDs and a quencher (analyte) lead to the formation of a nonfluorescent ground-state complex, which alters the absorption spectrum of LCQDs, generating a quantifiable response.…”
Section: Sensor and Biosensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches make CDs a sustainable and non-toxic alternative to metal-based quantum dots. However, most available organic molecules are still expensive, and their use and/or synthesis can pose significant challenges to the environment and to human health [ 19 ]. It has become quite desirable to use biomass waste as alternative precursors in the synthesis of CDs [ 20 ], given that biomass waste material is ubiquitous, nontoxic, cheap and renewable [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the above considerations, we have successfully developed a simple spray‐drying method to prepare N‐doped hollow porous carbon spheres (N‐HPCS) using biomass lignin as a carbon precursor because they widely exist in nature with high carbon content and plentiful chemical energy and cyanuric acid as an N dopant and a porogen [29] . The mass ratio of cyanuric acid to biomass lignin controls the lateral size, crystal structure, porosity, and pyrrolic‐N content.…”
Section: Introductionmentioning
confidence: 99%